What's Happening to Steelband Movement? - Hosein, Clyde (Trinidad Guardian)
The article laments the lack of commitment to the development of the steel pan and exodus of pan tuners who are migrating overseas to jobs which offer better standards of pay and better working conditions. Standardization of pan instruments is suggested to cope with the lost of pan tuners.
Keywords: Steel drum (Musical instrument) -- Standards -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel drum (Musical instrument) -- Tuning -- Trinidad and Tobago